2018
DOI: 10.1364/ol.43.002006
|View full text |Cite
|
Sign up to set email alerts
|

Nanobomb optical coherence elastography

Abstract: Wave-based optical elastography is rapidly emerging as a powerful technique for quantifying tissue biomechanical properties due to its noninvasive nature and high displacement sensitivity. However, current approaches are limited in their ability to produce high frequency waves and highly localized mechanical stress. In this work, we demonstrate that the rapid liquid-to-gas phase transition of dye-loaded perfluorocarbon nanodroplets (“nanobombs”) initiated by a pulsed laser can produce highly localized, high fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…For example, features with a lateral length of 20 μm in excised mouse aorta were observed with a measured equivalent Gaussian FWHM lateral feature resolution of approximately 10 μm to 15 μm [27], which is consistent with our framework. However, the diameter of many animal cells lies below 10 μm [49], and to study cells with a feature resolution below this limit will likely require solving more complex mechanical models, or indeed employing techniques that localize deformation [19][20][21][22]. The limit on achievable resolution may result in compression OCE being most useful in studying the mechanical properties over the entirety of the cell and the interactions between the cell and its environment over relatively large fields-of-view.…”
Section: Discussionmentioning
confidence: 99%
“…For example, features with a lateral length of 20 μm in excised mouse aorta were observed with a measured equivalent Gaussian FWHM lateral feature resolution of approximately 10 μm to 15 μm [27], which is consistent with our framework. However, the diameter of many animal cells lies below 10 μm [49], and to study cells with a feature resolution below this limit will likely require solving more complex mechanical models, or indeed employing techniques that localize deformation [19][20][21][22]. The limit on achievable resolution may result in compression OCE being most useful in studying the mechanical properties over the entirety of the cell and the interactions between the cell and its environment over relatively large fields-of-view.…”
Section: Discussionmentioning
confidence: 99%
“…The nanodroplets were synthetized from a liquid dodecafluoropentane core coated by a mixture of phospholipids and Cyanine 3 (Cy3) dye molecules. The formulation was adopted from a previously described protocol [28]. Briefly, 1,2-distearoyl-sn-glycero-3phosphocholine (DSPC), 1,2-distearoyl-sn-glycero-3-phosphoethanolamine-N-methoxypolyethyleneglycol-2000 (DSPE-PEG-2000), and cholesterol (all from Avanti Polar Lipids, Inc.) were dissolved in 2 mL of chloroform at a weight ratio of 90:8.5:1.5, respectively, and the total mass of 20 mg.…”
Section: Synthesis and Assessment Of Nanodropletsmentioning
confidence: 99%
“…In these studies, excitation of the nanodroplets occurs with nanosecond laser pulses, which are matched with the absorption band of an embedded dye, followed by a liquid to gas transition of the PFC core which elicits a strong photoacoustic signal. Using this principle, we recently demonstrated that the phase changing PFC nanodroplets can also be used to create localized, high frequency elastic waves in optical coherence elastography measurements [28,29]. PFC with relatively low boiling temperatures, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…To generate the elastic wave, the laser pulse should be efficiently absorbed and converted into heat by the tissue. Different techniques have been used to enhance the absorption of pulsed laser energy by the sample, such as the injection of nanoparticles, [35][36][37] droplets of perfluorocarbon, 38 and doping with graphite. 34 Naturally, the endogenous mechanism of the elastic wave generation would be preferred for many biological and clinical applications.…”
Section: Introductionmentioning
confidence: 99%